Age, period and cohort effects on alcohol‐related risky behaviours in Australia from 2001 to 2016. (21st October 2022) - Yuen, Wing See; Peacock, Amy; Man, Nicola; Callinan, Sarah; Slade, Tim; Farrell, Michael; Mattick, Richard; Livingston, Michael
Abstract: Aims: The aim of this study is to examine age, period and birth cohort trends in the prevalence of any alcohol‐related risky behaviour and to compare these trends between men and women. Design and setting: We used an age–period–cohort analysis of repeated cross‐sectional survey data from the Australian National Drug Strategy Household Survey from 2001 to 2016. Participants: Participants were 121 281 people aged 14–80 years who reported consuming alcohol in the past 12 months. Measurements: Any risky behaviour undertaken while under the influence of alcohol in the past 12 months (e.g. operating a motor vehicle) was measured: male or female. Findings: Controlling for age and cohort, cubic spline models showed that any alcohol‐related risky behaviour declined with time among participants who consumed alcohol [2016 versus 2007 rate ratio (RR) = 0.80, 95% confidence interval (CI) = 0.76–0.84]. Risky behaviour peaked in the 1954 birth cohort (1954 versus 1971 RR = 1.42, 95% CI = 1.30–1.55) and then steadily declined with more recent birth cohorts (2002 versus 1971 RR = 0.32, 95% CI = 0.27–0.39). Risky behaviour peaked at age 21 years, followed by steady decline and stabilization at approximately age 70 years. Males were overall twice as likely as females to report alcohol‐related risky behaviour (RR = 2.10, 95% CI = 1.84–2.39), but this effect was smaller in cohorts born after 1980 [1980 prevalence rate ratios (PRR) = 2.09, 95% CI = 1.81–2.43; 2002 PRR = 1.31, 95% CI = 1.03–1.68]. Conclusions: Alcohol‐related risky behaviour in Australia has declined generally since 2001, with rates for recent cohorts having the sharpest decline. Risky behaviour remains most prevalent in young adults, and the male–female gap in risky behaviour is closing for more recent birth cohorts. These trends are consistent with alcohol consumption trends observed in Australia and world‐wide.